Spermatozoa Morphology Examination Using Lenshooke SQA X1 Pro Compared with Manual Method - Adhipireno Purwanto; Edy Purwanto; Suyono Seso Sulijaya; Ismawatie Emma; Santoso Budi; Limijadi Edward Kurnia Setiawan (Universitas Nahdlatul Ulama Surabaya, 2022)
According to World Health Organization data, 30-40% of infertility is caused by male factors. The morphology of normal spermatozoa is an indicator of male fertility, and it is known by manual or automatic sperm analysis. Lenshooke SQA X1 PRO automatic equipment comes along with the development of laboratory equipment automation technology. The working principle of this tool is by shining light on the object of examination, then the camera with high resolution, with the facility of an optical lens will take a picture of the object. The database recorded by the camera is analyzed by the algorithm. The research objective was to test the suitability of the Lenshooke SQA X1 PRO automatic tool with manual method as the Gold Standard. Subjects in this study were patients who carried out semen analysis tests at the Clinical Pathology Laboratory of RSIA